Genotype-Phenotype Correlations and Characterization of Medication Use in Inherited Myotonic Disorders - Meyer, Alayne P.; Roggenbuck, Jennifer; LoRusso, Samantha; Kissel, John; Smith, Rachel M.; Kline, David; Arnold, W. David (Frontiers in Neurology, 2020)
Introduction: Inherited myotonic disorders are genetically heterogeneous and associated with overlapping clinical features of muscle stiffness, weakness, and pain. Data on genotype-phenotype correlations are limited. In this study, clinical features and treatment patterns in genetically characterized myotonic disorders were compared. Methods: A retrospective chart review was completed in patients with genetic variants in CLCN1, SCN4A, DMPK, and CNBP to document clinical signs and symptoms, clinical testing, and anti-myotonia medication use. Results: A total of 142 patients (27 CLCN1, 15 SCN4A, 89 DMPK, and 11 CNBP) were reviewed. The frequency of reported symptoms (stiffness, weakness, and pain) and electromyographic spontaneous activity were remarkably similar across genotypes. Most patients were not treated with anti-myotonia agents, but those with non-dystrophic disorders were more likely to be on a treatment. Discussion: Among the features reviewed, we did not identify clinical or electrophysiological differences to distinguish CLCN1 and SCN4A related myotonia. Weakness and pain were more prevalent in non-dystrophic disorders than previously identified. In addition, our results suggest that medical treatments in myotonic disorders may be under-utilized.